Goal tree model development of information control system of mini-hotels and its content - Левыкин, Виктор Макарович; Дэвон, Валерия Викторовна (Technology audit and production reserves, 2015)
Today the majority of domestic mini-hotels have difficulty in choosing and implementing of ICSH. This article is devoted to the development of the ICSH goal tree model because it is the first and most important and key step to determine the ICSH effectiveness. The authors have considered the problem of the introduction of IT in the hospitality and tourism business. The requirements for automated ICSH are analyzed. The main steps in the process of development and implementation of ICSH are determined. It is proposed context diagrams describing the structure of the system functioning of mini-hotels. The model of evaluating the effectiveness of ICSH is proposed. Solution of this problem allows the supervisor to mini-hotels make the right decision when choosing and implementing of ICSH. Through technical exchange of data for managers of mini-hotels now easier to create and sell packages of services to clients, solve problems of financial and operational management, marketing planning, improve competitiveness and expand its range of services. Applying ICSH, Internet, IT technologies, visionary hoteliers are able to maintain and develop the hotel business, improve service quality, increase competitiveness, reduce the cost of executing business processes. Automation services purchased a complex format and will affect all processes of functioning of mini-hotels and the relationship with the guests. Creation of integrated hotel information network, the center of which is a modern ICSH, minimizes the need to duplicate data and avoids errors that occur during manual data entry. Labor saving one or more employees several times the profit mini-hotels. Therefore, it is important the ICSH efficiency and goal tree development of IS of mini-hotel.